Analysis Of The Role Of Organizational Commitment As A Mediator In The Relationship Between Job Satisfaction And The Work Environment On Employee Performance - Yenni Christiani; Sutoyo; Koen Irianto Uripan; Sutomo; Immanuel Ustradi Osijo (PT Maju Malaqbi Makkarana, 2026)
This study aims to analyze the influence of job satisfaction and work environment on employee performance with organizational commitment as a mediating variable at the Samodra Ilmu Cendekia Foundation. This study uses a quantitative approach with the type of explanatory research to explain the causal relationship between variables. The population in this study is all employees of the Samodra Ilmu Cendekia Foundation, totaling 256 people, with sampling techniques using the census method. Data was collected through a questionnaire compiled based on the indicators of each variable and analyzed using the Partial Least Squares Structural Equation Modeling method. The results of the study show that job satisfaction has a positive and significant effect on employee performance, as well as a positive and significant effect on organizational commitment. The work environment has also been proven to have a positive and significant effect on employee performance and organizational commitment. However, the test results show that organizational commitment has no significant effect on employee performance. In addition, organizational commitment does not play a role as a mediating variable in the relationship between job satisfaction and the work environment on employee performance. These findings indicate that the influence of job satisfaction and the work environment on employee performance is direct, without going through an intermediary mechanism in the form of organizational commitment. Theoretically, the results of this study confirm that in the context of foundation-based education organizations, employee performance is more determined by proximal and situational factors, namely job satisfaction and work environment, than by long-term work attitudes such as organizational commitment. Organizational commitment is more appropriately positioned as an outcome of a work attitude oriented towards loyalty and sustainability of human resources, rather than as a direct predictor of performance. Practically, this study implies that efforts to improve employee performance at the Samodra Ilmu Cendekia Foundation will be more effective if they are focused on increasing job satisfaction and improving the work environment directly, while still paying attention to the role of organizational commitment in maintaining employee stability and loyalty.